Self-Determined Learning in Higher Education through PBL and Digital/Media - Bache, Manuel Alejandro Bejarano (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2024)
In a 2020/21 course and 2021/22 course, diverse pedadogic resources were applied. Learning-teaching styles usually are considered as a personal feature inherently linked to the teacher. For the presented courses, along the pandemic, not only did we use media resources to solve the issues and limitations for the learning-teaching process in higher education, but we also used an open field of teaching styles, displaying an ecologic style to increase inclusion, NdS, gender disparity, and, overally, reducing the limitations and possible negative impact due to cognitive, social, and basic human needs disparities, as well as starting level differences. The results can be seen in Bache, 2022a; Bache & Ries, 2021a; Bache et al., 2022). Hereby we present the ecologic approach as a way to inclusion and transcend the concept of teaching style to individualization and diversity inclusion (from teaching style as a feature to teaching styles as pedagogic resources) and the complex structres that emerged from the application of pedagogic resources, mostly regarding and linked to SDT and media, through PBL, PALS and Digital/Media resources.